Application of structural equation modelling to public health concern on psychosocial functioning and quality of life of adolescents in Nigeria (2019)
Structural equation modelling (SEM) is an efficient statistical method for the analysis and evaluation of complex research objectives involving relationships between observed and unobserved (latent) variables. Unfortunately, its application in Public Health research has been very limited in Nigeria. This paper documents basic theories, principles and application of SEM to research in Public Health with a focus on the psychosocial functioning and quality of life of adolescents in Nigeria. The cross-sectional study was conducted among adolescents (n=983) in Benue state, Nigeria. The study presents a step-by-step approach to SEM and also describes variety of research questions that SEM can be used to answer in public health domain with empirical application of SEM on psychosocial functioning and quality of life. Results of the empirical application showed that poor psychosocial functioning negatively impacts the quality of life of adolescents in Nigeria. There is need to encourage researchers in public health to apply SEM in their research.